Investigation on the Combined Effect of Fibers and Cement on the Mechanical Performance of Foamed Bitumen Mixtures Containing 100% RAP - Ehsan Ashouri Taziani; Emanuele Toraldo; Filippo Giustozzi; Maurizio Crispino (Advances in Materials Science and Engineering)
Concerns about virgin aggregate sources and increasing demands for construction materials of transport infrastructures as the key parameters in development are the most important reasons, which convinced pavement engineers to develop new methods in order to use higher amount of recycled asphalt pavement (RAP). One of the common methodologies to produce mixtures containing RAP is foamed bitumen mix (FBM). In addition, according to previous research studies, incorporating various types of fibers and hydraulic binders such as cement could significantly improve the mechanical performance of mixtures. The present research study evaluated FBM containing 100% RAP and two types of fiber and Portland cement. Dynamic modulus, unconfined dynamic creep compression, and indirect tensile strength were evaluated in the laboratory at optimum moisture content, which was investigated in this research. Both types of fiber and cement proved to enhance specific properties of mixtures.